School Scientific Argumentation Enriched by Digital Technologies: Results With Pre- and in-Service Science Teachers - Garcia Romano, Leticia; Occelli, Maricel; Adúriz-Bravo, Agustín (Eurasia Journal of Mathematics, Science and Technology Education, 2021)
This article focuses on the integration of argumentation and digital technologies in science teacher education. We present theoretical reflections, results of empirical research, and description of innovative experiences with pre- and in-service biology teachers. Regarding argumentation, we analyse what defending a claim in science entails for teachers, the teaching strategies they (would) use in the classroom in relation to argumentation, the relevance that they attribute to the performance of different tasks for arguing, the subject content where argumentation fits more suitably, and the reasons they would consider in favour of arguing in science classes. For the analysis of educational practices that involve use of technologies, we adopt a perspective that looks at their complexity and recognises teachers as their creative authors. We discuss the way in which teachers (would) use technologies in their practice, their expectations around this, and the foreseen results with students. Finally, we examine three innovative educational experiences already implemented, using argument maps, web-based inquiry, and a digital game. We look into the possibilities that these technological resources offer for teachers to analyse the argumentation levels reached by their students.